Wildlife and Hunting As Alternative Farm Enterprises - William M. Giuliano; Kristin C. Thomas (EDIS)
Wildlife enhances our quality of life and is an integral part of the landscape. In addition, wildlife can be managed to provide revenue as part of alternative farm enterprises. The key to maintaining healthy wildlife populations necessary in such alternative enterprises is providing quality habitat through proper management (Figure 1). This document is WEC 197 and one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published: July 2005.